Implikasi Sentralisasi Pengawas Ketenagakerjaan Dari Kab/Kota Ke Provinsi - Fadjri Fadjri (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2017)
A centralized review of labor inspectors from districts/ municipalities to provincial governments is intended to clarify the required policy consequences. Methods used by study desk and in-depth discussion with competent resource persons in some areas. The development of the capacity of human resources and institution is a non- negotiable implication for the optimal functioning of the labor inspector.